Predictors of cannabis and tobacco co-use in youth: exploring the mediating role of age at first use in the population assessment of tobacco health (PATH) study - Smith, Crystal Lederhos (J Cannabis Res, 2021)
BACKGROUND: Adolescents often use substances such as tobacco and cannabis. Co-use of these substances can lead to physical, mental, and psychosocial difficulties beyond that which would be anticipated by simple additivity of their individual effects. METHODS: We aimed to examine the mediating role of age at first use of cannabis or tobacco (AU) between youth factors of internalizing, externalizing, and sensation seeking and two co-use outcomes (lifetime; last 30 days). Path analytic modeling using data from youth age 12–17 who had tried cannabis or tobacco at least once in their lives and participated in the Population Assessment of Tobacco Health (PATH) waves one and two (collected 2013–2015; n=3,847; approximately 46% female) study allowed us to examine these relationships. RESULTS: The lifetime use model indicated significant direct (internalizing (B = 0.18), externalizing (B = 0.30), sensation seeking (B = 0.15)) and indirect relationships (internalizing (B = 0.18), externalizing (B = 0.33), sensation seeking (B = 0.10)) between each of the three youth factors, the mediator (AU) and the lifetime co-use outcome (p < 0.05 for all). A direct relationship between AU and lifetime co-use was also observed (B = − 1.54). In the past 30-day use model, significant direct paths from AU (B = − 0.49) and sensation seeking (B = 0.06) to past 30-day use were present (p < 0.05 for all). DISCUSSION: Examination of mediation by AU in the relationships between youth factors and youth co-use of cannabis and tobacco is an important step in understanding these complex relationships. This study is strengthened by the use of a large, nationally representative sample, yet is limited by several factors, such as the use of a secondary dataset and the use of youth self-report. CONCLUSIONS: Based on the findings, programs or interventions targeting youth factors of internalizing, externalizing, and sensation seeking as well as interventions aiming to stave off AU should promote decreased tobacco and cannabis co-use. Sensation seeking and AU appear to be the most influential factors and should be considered when developing and promoting prevention policies/programs for higher risk youth populations.